Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

henaoalexandra

  • 3 years ago

p=a+b+2c a=

  • This Question is Closed
  1. blurbendy
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    p = a + b + 2c p - b = a + 2c a = p - b - 2c

  2. msoemosharro
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    p = a + b + 2c add -p to both sides of the equation p - p = a+b+2c-p 0=a+b+2c-p add-a to both sides of the equation -a=a-a+b+2c-p -a=0+b+2c-p multiply by (-1) both sides of the equation (-1)(-a)=(-1)(b+2c-p) a=-b-2c+p rearrange and you get: a=p-b-2c

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy